INTERNALISASI AKHLAKUL KARIMAH MELALUI KURIKULUM PENDIDIKAN ISLAM DI ERA DIGITAL - Pratama, Irja Putra; Isro, Arsan; Nurusshomad, Nurusshomad; Yana, Virda; Purnomo, Eko (Raudhah - Proud To Be Professional, 2024)
The development of the digital era presents significant challenges for Islamic education in internalizing the values of akhlakul karimah among Madrasah Tsanawiyah students. Exposure to negative content, low digital literacy, and distractions in learning are significant obstacles to shaping the Islamic character of the younger generation. This study aims to analyze the challenges and formulate innovative strategies for implementing an Islamic education curriculum relevant to the needs of the digital era. Using a library study approach, the study synthesizes theoretical insights from primary and secondary literature through content analysis of recent publications. The results reveal that integrating digital technologies, such as Islamic applications, Islamic value-based e-learning, and interactive media, can support the internalization of akhlakul karimah. Project-based and contextual learning approaches also enhance students’ understanding and practice of Islamic values. Furthermore, collaboration between schools, families, and communities is key to creating an educational environment that shapes students’ Islamic character. The main challenges in implementing these strategies include low digital literacy, limited technological infrastructure, and stakeholder coordination. This study emphasizes the importance of holistic and adaptive strategies in addressing the complexities of the digital era. Through the synergy between technological innovation, active learning, and multi-stakeholder collaboration, Islamic education can effectively shape a generation with akhlakul karimah while remaining responsive to the dynamics of the times.